Planting date and tillage effects on yield and nutrient uptake of two sorghum cultivars grown in sub-humid and semi-arid regions in South Africa - Mrubata, Kaya; Nciizah, Adornis Dakarai; Muchaonyerwa, Pardon (Frontiers in Agronomy, 2024)
IntroductionSorghum is emerging as a viable crop option to increase food production under changing climate due to its resilience to drought and marginal soils. Appropriate planting date, crop cultivars, type of tillage and rotations, under contrasting climatic conditions, could make significant contribution on the effective management of sorghum under changing climatic conditions. A short-term study was carried out to investigate the effects of planting date, crop cultivar, tillage type and rotations on the growth and primary nutrient uptake of sorghum in contrasting climatic regions.MethodsThe study was conducted in Free State - (FS) and KwaZulu Natal (KZN) Provinces of South Africa over two seasons (2020/21 and 2021/22). The two cultivars (Pan8816 and Macia) were sown in December (PD1) and in January (PD2) under conventional tillage (CT) and no-till (NT) and with two rotations (Sorghum-Cowpea-Sorghum and Sorghum-Sorghum-Sorghum) resulting in 2×2×2×2 factorial experiment.Results and discussionIn KZN, in both the first (2020/21) and second (2021/22) seasons, the effects of all the factors, except cultivar in the second season, were not significant on yield, and uptake of nitrogen (N), phosphorus (P) and potassium (K). In the second season, Pan8816 (4.40 t/ha) produced 3.3 times higher yield than Macia (1.32 t/ha), and took up higher N, K and P. In FS, the early planted sorghum (1.15 t/ha for season one; 3.39 t/ha for season two) had significantly higher yield than late planted sorghum (0.434 and 0.91 t/ha for seasons one and two, respectively). Furthermore, the early-planted crops took up higher N, K and P than when planted late, while Pan8816 took up 1.74 times more P than Macia. Plants grown under CT (2.61 t/ha) produced significantly higher yield than under NT (1.70 t/ha), with plants under CT taking up significantly more K than those grown on NT. These findings suggest that in the drier FS, early planting under conventional tillage, while in the wetter KZN, selecting the appropriate cultivar (PAN8816), are essential for sorghum grain yield, at least in the short-term.